Sex affects the nestling diet of a large aerial predator of the Andes - Juan Sebastián Restrepo-Cardona; Sebastián Kohn; Juan D. Vásquez-Restrepo; Luis A. Salagaje; Fabricio Narváez; Paul Monar-Barragán; Félix Hernán Vargas; Vanessa Hull (Scientific Reports)
Abstract In raptors, size-related differences between sexes affect the choice of prey. While the broad patterns of the globally endangered black-and-chestnut eagle’s (Spizaetus isidori) feeding habits are known in the northern Andes, specific knowledge of the sex-related diet differences in the species remains unknown. Here, we conducted direct observations to evaluate the differences in prey size between female and male eagles, as well as the numerical rates of prey delivery to nestlings, and the differences in prey diversity between sexes, in nine nests in Ecuador. Males provided more prey to nestlings than females (227 vs. 99 prey items, respectively), and females hunted heavier prey than males (on average 1.19 vs. 0.95 kg, respectively). The overlap in captured prey between sexes was relatively high (O = 0.67), which suggests potential for competition. There was no difference between male and female black-and-chestnut eagles in either prey diversity or the composition of the prey species when considering the main prey items. However, the sexes differed in the prey items at lower biomass contributions. Males’ prey were primarily bird species from the orders Galliformes, Columbiformes, and Psittaciformes, while females’ prey were mostly mammal species from the orders Primates and Carnivora, and some passerine birds. Both sexes preferred arboreal species, but males hunted more scansorial and terrestrial prey. Our data suggest that sex-related differences in the eagle’s dietary contribution to nestlings likely result from parental role differentiation, rather than intersexual competition.